An analysis of changes to transit accessibility and equity after the opening of a bus rapid transit system in Hartford, Connecticut - Bertolaccini, Kelly Layne (Journal of Transport and Land Use, 2018)
In March 2015, CTfastrak, a bus rapid transit system operating in Connecticut in the United States, opened after nearly 16 years of planning and controversy. The 15.1-km (9.4-mi) busway connects the town of New Britain to the state capital of Hartford. The analysis conducted in this paper investigates whether or not CTfastrak and the transit system restructuring that occurred between 2013 and 2016 improved overall transit accessibility in the region, and if so, whether or not the distribution of these improvements is equitable. This exploration provides strong evidence that overall transit accessibility has improved in the region. Horizontal, or spatial equity, did worsen slightly as a result of this highly localized project. However, vulnerable populations experience more improvements and fewer decreases in transit accessibility than the general population. Though these analyses seem promising, an analysis of the distribution of transit access among workers hints that while many people are experiencing increases in general accessibility, they may not have meaningful access to their place of employment.